Mathematical model for Chikungunya disease with two types of Aedes mosquitoes - Pongsumpun, Puntipa; Pongsumpun, Puntani (My University, 2022)
Chikungunya disease is occurred when the infected Aedes mosquitoes bite. Chikungunya virus is a member of the genus Alphavirus family Togaviridae. There are 2 species of Aedes mosquitoes such as Aedes aegypti and Aedes albopictus. We describe the transmission of the disease by using mathematical model. We separated the populations to human and vector populations. We separate the human population to susceptible, infectious and recovered populations. The mosquitoes are separated into susceptible and infectious populations. Then we analyze the model by using standard dynamical analysis. The numerical solutions are shown to see the stability of each equilibrium state. The variances of each parameter are shown to see the behavior of each population. The basic reproduction number of this disease is shown to reduce the transmission of this disease.
Keywords: Chikungunya disease; local stability; mathematical model; numerical solution